The Implementation of the 2006 Curriculum in Teaching English at State Junior High School 1 in Kalikajar - Indah Wulandari (Universitas Sarjanawiyata Tamansiswa, 2019)
Two major objectives are targeted in this research, method applied in English language teaching and how to implement the method. The research was conducted at State Junior High School 1 in Kalikajar in 2015. The subjects of this research were three English teachers at the school. The data for this research were collected through document, classroom observation, and interview. The result revealed the method claimed by the teachers were Total Physical Response (TPR) and Presentation, Practice, Production (PPP). Methods written on the lesson plan were categorized onto none implemented, partially implemented, and fully implemented in the teaching process. Findings shows that what was written on the lesson plan was not always implemented in the English language teaching and learning.